Electron-phonon coupling in La3In under pressure. (21st June 2023) - Singh, Surinder; Pinsook, Udomsilp
Abstract: Conventional superconducting parameters Eliashberg spectral function, phonon DOS, average electron-phonon coupling constant & superconducting transition temperature of La3 In were calculated at ambient and applied positive hydrostatic pressure. Ambient pressure electron-phonon coupling constant was found to be 1.43 and superconducting transition temperature was calculated to be 8.7 K which is close to the experimental reported value of 9.5 K. Logarithmic average phonon frequency at ambient pressure was found to be 6.21 × 10 −3 eV. Phonon dispersion relations for the ambient and applied positive hydrostatic pressure were calculated to confirm the dynamical stability of La3 In under positive pressure. Acoustic modes of vibrations were found to mediate most of the electron-phonon-electron interaction with a very small contribution from optical modes of vibrations. Fermi surface at ambient pressure was also calculated and employed in explaining the large value of the calculated electron-phonon coupling constant. The effect of spin–orbit coupling on electronic, phonon and superconducting properties of La3 In was also studied.